2020
DOI: 10.1039/d0tb01106a
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular delivery of therapeutic antisense oligonucleotides targeting mRNA coding mitochondrial proteins by cell-penetrating peptides

Abstract: Cell-penetrating peptides are a promising therapeutic strategy for a wide variety of degenerative diseases, ageing, and cancer. Among the multitude of cell-penetrating peptides, PepFect14 has been preferentially used in our...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 64 publications
0
14
0
Order By: Relevance
“…In the last decade, there has been a crescendo of interest in the development of suitable nano-delivery systems to carry genetic content into the proximity of mitochondria and ensure its long-term expression, a strategy to deal with diseases related to mtDNA mutations [19,20,[40][41][42][43][44]. In this work, peptide/pND1 complexes have been developed aiming to target mitochondria and deliver pND1 plasmid into this organelle, as the first step for efficient mitochondrial gene expression.…”
Section: Pnd1 Complexation Capacitymentioning
confidence: 99%
See 1 more Smart Citation
“…In the last decade, there has been a crescendo of interest in the development of suitable nano-delivery systems to carry genetic content into the proximity of mitochondria and ensure its long-term expression, a strategy to deal with diseases related to mtDNA mutations [19,20,[40][41][42][43][44]. In this work, peptide/pND1 complexes have been developed aiming to target mitochondria and deliver pND1 plasmid into this organelle, as the first step for efficient mitochondrial gene expression.…”
Section: Pnd1 Complexation Capacitymentioning
confidence: 99%
“…In the past few years, several research studies have demonstrated efficient mitochondria targeting [19,40,43,44,[50][51][52] The efforts in the development of delivery systems displaying this capacity have been fruitful, with various reports on biomolecules or gene delivery into mitochondria [19,39,[53][54][55]. Despite this achieved progress, to date, few works have demonstrated effective long-term mitochondrial transgene expression [52].…”
Section: Mitochondria Targeting Abilitymentioning
confidence: 99%
“…The results showed that the vaccine augments Th1 (type 1 helper T-cell)-biased CD4 T-cell responses. Additionally, undetectable or very low Th2 or CD8 T-cell responses were noted ( 132 ).…”
Section: Covid-19 Mrna Vaccinesmentioning
confidence: 99%
“…A bit earlier, Szeto and Schiller introduced cell-permeable, mitochondrial-targeted peptides [129,130], which were grafted onto different polymer-based nanoparticles, but not onto PBNs. Based on the Szeto-Schiller peptide SS-31, Prof. Langel's group developed a set of mitochondrialpenetrating peptides based on the covalent fusion of PF14 and mtCPP1 [131] for antisense oligonucleotide (ASO) delivery [132]. In this report, the specific delivery of peptide/oligonucleotide nano-complexes were shown as proof-of-principle for the potent therapeutic application to patients with mitochondrial diseases.…”
Section: Organelle Targetingmentioning
confidence: 99%